Clean Water Distribution Network Analysis Using Epanet 2.0 (Case Study of Housing Telkomas Tamalanrea District) - Marlan Nathan; Erni Rante Bungin; Herman Welem Tanje (Paulus Civil Engineering Journal, 2022)
Telkomas Housing is one of the complexes located in Tamalanrea District, Makassar City, South Sulawesi Province, and is an area that gets clean water distribution from Makassar City PDAM, but Telkomas Housing currently has a problem regarding water pressure. This research is intended to determine the need for clean water in Telkomas housing at present and in the future and make plans for the development of clean water distribution with the development of Telkomas housing. The results of the calculation of current water needs in Telkommas housing with the number of houses that are subscribed to are 405 houses, where the average daily water requirement is 340,200 liters/day, the average daily requirement is 391,230 liters/day and the peak hour is 7,924 liters/second. Then on the calculation of future water needs which is assumed to be 10 years in the future and the number of customers is 70% or about 770 houses, 2 educational facilities, and 3 religious facilities, where the average daily water requirement is 673,080 liters/day, the maximum daily requirement is 774,042 liters /day and peak hours of 15.678 liters/second. Then after analyzing the piping network on Epanet 2.0, there are several nodes whose pressure is still below the distribution pipe criteria or about 5.16 meters of water. each reservoir so that the water pressure value obtained has met the distribution pipe criteria and has been able to meet the water needs of PDAM customers in Telkomas housing both now and in the future.